Structure and individual anatomical variability of the I-III lobules of the human cerebellar hemispheres. - Stepanenko, O. Yu.; Maryenko, N. I. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Morphological changes of cerebellar lobules are found in many congenital and acquired diseases of the cerebellum. In recent years, thanks to modern imaging techniques morphological changes of the hemispheric and vermal lobules can be detected in vivo. However, criteria of imaging diagnostic methods which are based on information about normal structure of the cerebellum, do not take into account the features of individual anatomical variability, gender and age characteristics. Objective - to investigate individual variability and features of variant anatomy of the I-III lobules of the human cerebellar hemispheres. Methods. Research was conducted at the Kharkiv regional bureau of forensic medicine on 100 cerebellums of people of both sexes 20-99 years old who died of causes unrelated to brain pathology. During the forensic autopsy the cerebellum and brain stem were separated and fixed during one month in 10% formalin solution. Parasagittal sections of cerebellar hemispheres were investigated. Results. The shape of the I-III lobules of the human cerebellar hemispheres is quite varied. Differences of the structure of these lobules depend on the characteristics of the branching of the white matter, the number of secondary branches and cerebellar folia. We described 4 variants of the shape of the II-III lobules of the human cerebellar hemispheres; 3rd variant is the most common. That variant can be used as anatomical standard of the lobules. Conclusion. Described variants of the shape of the cerebellar lobules can be used as criteria standards in current imaging techniques for the diagnostics of various diseases of the CNS.